Kangaroo Mother Care in Improving Thermoregulation of Premature Babies During the COVID-19 Pandemic: A Case Report - Wahyuningrum, Ari Damayanti; Arief, Yuni Sufyanti; Fitriyasari PK, Rizki; Lei, Chui Ping; Kapti, Rinik Eko (UI Scholars Hub, 2023)
Premature babies lose four times more heat than those with sufficient birth weight. Moreover, their body temperature regulation center does not function properly. This study aimed to investigate Kangaroo Mother Care's effect in increasing premature babies' thermoregulation during the COVID-19 pandemic at Hospital A in Malang City, Indonesia. This study was a case report with data from follow-up checks on premature babies discharged from the hospital. The Kangaroo Mother Care method, carried out by the mother, increased the thermoregulation of premature babies' temperature by 0.2ᴼC compared to the father. It was because women have a slightly higher body temperature than men. The comfortable body temperature for women was 2.5ᴼC higher than for men. Men had a lower body mass of fat, so it took an average longer time for metabolism. The kangaroo mother care procedure, especially when done by the mother, can increase the body temperature of premature babies by conduction.